ALMOST CONTACT B-METRIC STRUCTURES AND THE BIANCHI CLASSIFICATION OF THE THREE-DIMENSIONAL LIE ALGEBRAS (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2015)
The object of investigation are the almost contact manifolds with B-metric in the lowest dimension three, constructed on Lie algebras. It is considered a relation between the classes in the Bianchi classification of three-dimensional real Lie algebras and the classes of a classification of the considered manifolds. There are studied some geometrical characteristics in some special classes.